2010
DOI: 10.1074/jbc.m109.057182
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Calcineurin-mediated Endocytosis and α-Amino-3-hydroxy-5-methyl-4-isoxazolepropionic Acid (AMPA) Receptors Prevents Amyloid β Oligomer-induced Synaptic Disruption

Abstract: Synaptic degeneration, including impairment of synaptic plasticity and loss of synapses, is an important feature of Alzheimer disease pathogenesis. Increasing evidence suggests that these degenerative synaptic changes are associated with an accumulation of soluble oligomeric assemblies of amyloid ␤ (A␤) known as ADDLs. In primary hippocampal cultures ADDLs bind to a subpopulation of neurons. However the molecular basis of this cell type-selective interaction is not understood. Here, using siRNA screening techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
171
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(179 citation statements)
references
References 84 publications
6
171
2
Order By: Relevance
“…Other studies have focused on the functional interactions between A␤ peptide and glutamate receptors (Decker et al, 2010b;Hu et al, 2009;Texidó et al, 2011;Zhao et al, 2010) or have attempted to reinforce neuronal defenses through the neurotrophic effects of growth factors or membrane lipids such as docosahexaenoic acid (Ma et al, 2009). Many NMDA receptor modulators have been characterized and are potential therapeutics for Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have focused on the functional interactions between A␤ peptide and glutamate receptors (Decker et al, 2010b;Hu et al, 2009;Texidó et al, 2011;Zhao et al, 2010) or have attempted to reinforce neuronal defenses through the neurotrophic effects of growth factors or membrane lipids such as docosahexaenoic acid (Ma et al, 2009). Many NMDA receptor modulators have been characterized and are potential therapeutics for Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, disruption of AMPAR trafficking by soluble amyloid beta (Aβ) oligomers is a major causative agent of synaptic dysfunction in AD 144 . More specifically, it has been reported that Aβ oligomers bind in close proximity to GluA2-containing complexes and AMPAR antagonists inhibit Aβ oligomer binding and synaptic loss, raising the possibility that Aβ may affect AMPAR trafficking by binding directly to the GluA2 protein complex 145 . Conversely, intracellular application of oligomerised Aβ causes an acute increase in AMPAR-mediated synaptic responses, which requires PKA phosphorylation of S845 in GluA1.…”
Section: Ampar Subunits and Diseasementioning
confidence: 99%
“…Accordingly, several reports have shown that oA␤ inhibited LTP and facilitated LTD (5,6,(17)(18)(19), probably by inducing internalization of NMDAR and AMPAR (13,16,17). Although changes in [Ca 2ϩ ] i are important to trigger LTP or LTD (7), the effect of oA␤ on the intracellular calcium levels and its contribution to the deregulation of LTP and LTD are still a controversial issue (20).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%
“…Increasing the extrasynaptic pool of AMPAR has been proposed to be a critical event for the establishment of LTP (12). Recent reports have shown that oA␤ could alter AMPAR endocytosis by modulating downstream kinases and phosphatases (13)(14)(15).…”
Section: Alzheimer Disease (Ad)mentioning
confidence: 99%